Antimicrobial activity of Terpenes against slime producing and non producing Staphylococci - Gallucci, Mauro Nicolas (2010)
Staphylococcus aureus, responsible of several diseases in humans and animals, produce virulence factors like an extracelullar polysacharide or “slime”. Methicillin resistant S. aureus (MRSA) is able to resist -lactamic antibiotics and eventually is a slime producer. Conventional chemotherapics against MRSA are ineffective. Essential oils (EOs) are oily liquids obtained from aromatic plants chemically constituted by terpenes. Their antimicrobial activity against clinical and foodborned pathogenic bacteria has been described. The aim of this work was to study the inhibitory activity of terpenes on slime producing Staphylococcus aureus methicillin sensitive (MSSA) and MRSA. Terpenes were tested against MRSA and MSSA with the resazurin microdilution assay. The terpenes active against all the microorganisms were carvacrol, thymol, geraniol and eugenol. Carvone was only active against S. aureus MSSA, while citronellol, menthol, menthone and myrcene did not show antimicrobial activity. The terpenes active against MRSA when slime was induced were carvacrol, eugenol, geraniol and thymol. This strain showed activity of carvacrol, carvone, eugenol, geraniol and thymol when slime was not induced. The results obtained clearly showed that carvacrol and thymol had the best antimicrobial activity. Carvacrol, eugenol and thymol could be used for therapeutical formulations in replacement of antibiotic to treat diseases caused by resistant microorganisms such as MRS.